Predictive factors of multiple sclerosis relapse after the first demyelinating event: A 5-year follow-up - Kolčava, Jan; Pelíšek, Ondřej; Vlčková, Eva (Multiple sclerosis and related disorders, 2023)
There is a growing need to discover the characteristics that predict prognostic factors after the first demyelinating event. In this study of 141 patients that met the 2017 McDonald criteria, a higher number of oligoclonal bands, cervical spinal cord demyelinating lesions, and sensory involvement were identified as independent predictors of the second demyelinating event during the 5-year follow-up period in patients who experienced the first demyelinating event. The identification of the aforementioned risk variables will make it possible to identify patients who are more likely to exhibit early second demyelinating event, implying more frequent monitoring and consideration of early application of highly effective disease-modifying treatment.
Keywords: Magnetic Resonance Imaging; Chronic Disease; Oligoclonal Bands; magnetická rezonanční tomografie; oligoklonální proužky; Humans; demyelinizační nemoci; roztroušená skleróza; Follow-Up Studies; lidé; Demyelinating Diseases; chronická nemoc; Multiple Sclerosis; následné studie; nemoci míchy; Spinal Cord Diseases